Theology and the enlightenment a critical enquiry into enlightenment theology and its reception - Avis, Paul 1947- (London Bloomsbury Publishing Plc, 2022)
Cover -- Contents -- Preface -- Abbreviations -- 1 Engaging the Enlightenment -- 2 Scapegoating the Enlightenment -- 3 A virtuous Enlightenment -- 4 The Enlightenment and religion -- 5 The Anglican Enlightenment -- 6 Enlightenment history and the Bible -- 7 The Enlightenment in the frame of Christian theology -- Bibliography -- Index of Names.
Description based on publisher supplied metadata and other sources
Keywords: Enlightenment; Theology-History-18th century; Electronic books